Stressful life events and depressive symptoms among symptomatic long QT syndrome patients. (April 2016) - Hintsa, Taina; Jokela, Markus; Elovainio, Marko; Määttänen, Ilmari; Swan, Heikki; Hintsanen, Mirka; Toivonen, Lauri; Kontula, Kimmo; Keltikangas-Järvinen, Liisa
We examined whether long QT syndrome status moderates the association between stressful life events and depressive symptoms. Participants were 562 ( n = 246 symptomatic) long QT syndrome mutation carriers. Depressive symptoms were measured with a modified version of the Beck's Depression Inventory. There was an interaction between long QT syndrome status and stressful life events on depressive symptoms. In the symptomatic long QT syndrome patients, stressful life events were associated with depressive symptoms ( B = 0.24, p < 0.001). In the asymptomatic long QT syndrome mutation carriers, this association was 62.5 percent weaker ( B = 0.09, p = 0.057). Compared to asymptomatic long QT syndrome mutation carriers, symptomatic long QT syndrome patients are more sensitive to the depressive effects of stressful life events.